1998
DOI: 10.1191/026921698677124622
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care in chronic obstructive airways disease: a needs assessment

Abstract: The view that palliative care should move beyond cancer is widely endorsed, however, there remains a lack of clarity about the level at which this should occur. In order to target the palliative approach effectively, the value of more detailed and localized needs assessment becomes apparent. This paper provides evidence from a study commissioned by a department of public health, where the focus was the palliative care needs of an individual with chronic obstructive airways disease (COAD). Over a six-month peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
1
9

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(156 citation statements)
references
References 16 publications
5
141
1
9
Order By: Relevance
“…A recent study of patients with COPD or lung cancer in the US Veterans Affairs Health System also found that patients with COPD were much more likely to be admitted to an ICU, and have greater lengths of stay in the ICU during their terminal hospitalisation, than patients with lung cancer. In the same study, significant geographic variation in ICU utilisation was found for patients with COPD [15]. Although variation in care may be influenced by many factors including availability, access and reimbursement issues, such geographic variation suggests a lack of consensus concerning the best approach to palliative and endof-life care for patients with COPD.…”
Section: Poor Palliative Care In Copd and The Link To Poor Communicationmentioning
confidence: 78%
“…A recent study of patients with COPD or lung cancer in the US Veterans Affairs Health System also found that patients with COPD were much more likely to be admitted to an ICU, and have greater lengths of stay in the ICU during their terminal hospitalisation, than patients with lung cancer. In the same study, significant geographic variation in ICU utilisation was found for patients with COPD [15]. Although variation in care may be influenced by many factors including availability, access and reimbursement issues, such geographic variation suggests a lack of consensus concerning the best approach to palliative and endof-life care for patients with COPD.…”
Section: Poor Palliative Care In Copd and The Link To Poor Communicationmentioning
confidence: 78%
“…They may describe disabling shortness of breath, depression, cough, fatigue, pain, confusion, anorexia, or thirst [5][6][7][8]. This morbidity is reflected in severe impairment of quality of life and activities of daily living [5,6,9]. Social isolation is common [5].…”
Section: Introductionmentioning
confidence: 99%
“…This morbidity is reflected in severe impairment of quality of life and activities of daily living [5,6,9]. Social isolation is common [5]. Exacerbations may result in frequent hospital admissions and high use of primary care services [5,9] C o p y r ig h t G e n e r a l P r a c t ic e A ir w a y s G r o u p R e p r o d u c t io n p r o h ib it e d is high, but less than half have access to appropriate social and nursing support [5][6][7]9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors argue that this can be a consequence of the fact that healthcare professionals do not take psychosocial and existential needs into account and preferentially focus only on the physical aspects of COPD (Au et al, 2006;Skilbeck et al, 1998). An example in the present study is the daughter whose mother had recurrent periods of confusion.…”
Section: Discussionmentioning
confidence: 99%